Activation of SIK1 by phanginin A inhibits hepatic gluconeogenesis by increasing PDE4 activity and suppressing the cAMP signaling pathway - Siwen Liu; Suling Huang; Xingde Wu; Ying Feng; Yu Shen; Qin-shi Zhao; Ying Leng (Elsevier, 2020)
Objective: Salt-induced kinase 1 (SIK1) acts as a key modulator in many physiological processes. However, the effects of SIK1 on gluconeogenesis and the underlying mechanisms have not been fully elucidated. In this study, we found that a natural compound phanginin A could activate SIK1 and further inhibit gluconeogenesis. The mechanisms by which phanginin A activates SIK1 and inhibits gluconeogenesis were explored in primary mouse hepatocytes, and the effects of phanginin A on glucose homeostasis were investigated in ob/ob mice. Methods: The effects of phanginin A on gluconeogenesis and SIK1 phosphorylation were examined in primary mouse hepatocytes. Pan-SIK inhibitor and siRNA-mediated knockdown were used to elucidate the involvement of SIK1 activation in phanginin A-reduced gluconeogenesis. LKB1 knockdown was used to explore how phanginin A activated SIK1. SIK1 overexpression was used to evaluate its effect on gluconeogenesis, PDE4 activity, and the cAMP pathway. The acute and chronic effects of phanginin A on metabolic abnormalities were observed in ob/ob mice. Results: Phanginin A significantly increased SIK1 phosphorylation through LKB1 and further suppressed gluconeogenesis by increasing PDE4 activity and inhibiting the cAMP/PKA/CREB pathway in primary mouse hepatocytes, and this effect was blocked by pan-SIK inhibitor HG-9-91-01 or siRNA-mediated knockdown of SIK1. Overexpression of SIK1 in hepatocytes increased PDE4 activity, reduced cAMP accumulation, and thereby inhibited gluconeogenesis. Acute treatment with phanginin A reduced gluconeogenesis in vivo, accompanied by increased SIK1 phosphorylation and PDE4 activity in the liver. Long-term treatment of phanginin A profoundly reduced blood glucose levels and improved glucose tolerance and dyslipidemia in ob/ob mice. Conclusion: We discovered an unrecognized effect of phanginin A in suppressing hepatic gluconeogenesis and revealed a novel mechanism that activation of SIK1 by phanginin A could inhibit gluconeogenesis by increasing PDE4 activity and suppressing the cAMP/PKA/CREB pathway in the liver. We also highlighted the potential value of phanginin A as a lead compound for treating type 2 diabetes.